Essential role of a carboxyl‐terminal α‐helix motif in the secretion of coagulation factor XI. (10th February 2021) - Hayakawa, Yuri; Tamura, Shogo; Suzuki, Nobuaki; Odaira, Koya; Tokoro, Mahiru; Kawashima, Fumika; Hayakawa, Fumihiko; Takagi, Akira; Katsumi, Akira; Suzuki, Atsuo; Okamoto, Shuichi; Kanematsu, Takeshi; et al.
Abstract: Background: Coagulation factor XI (FXI) is a plasma serine protease zymogen that contributes to hemostasis. However, the mechanism of its secretion remains unclear. Objective: To determine the molecular mechanism of FXI secretion by characterizing a novel FXI mutant identified in a FXI‐deficient Japanese patient. Patient/Methods: The FXI gene ( F11 ) was analyzed by direct sequencing. Mutant recombinant FXI (rFXI) was overexpressed in HEK293 or COS‐7 cells. Western blotting and enzyme‐linked immunosorbent assay were performed to examine the FXI extracellular secretion profile. Immunofluorescence microscopy was used to investigate the subcellular localization of the rFXI mutant. Results: We identified a novel homozygous frameshift mutation in F11 [c.1788dupC (p.E597Rfs*65)], resulting in a unique and extended carboxyl‐terminal (C‐terminal) structure in FXI. Although rFXI‐E597Rfs*65 was intracellularly synthesized, its extracellular secretion was markedly reduced. Subcellular localization analysis revealed that rFXI‐E597Rfs*65 was abnormally retained in the endoplasmic reticulum (ER). We generated a series of C‐terminal–truncated rFXI mutants to further investigate the role of the C‐terminal region in FXI secretion. Serial rFXI experiments revealed that a threonine at position 622, the fourth residue from the C‐terminus, was essential for secretion. Notably, Thr622 engages in the formation of an α‐helix motif, indicating the importance of the C‐terminal α‐helix in FXI intracellular behavior and secretion. Conclusion: FXI E597Rfs*65 results in the pathogenesis of a severe secretory defect resulting from aberrant ER‐to‐Golgi trafficking caused by the lack of a C‐terminal α‐helix motif. This study demonstrates the impact of the C‐terminal structure, especially the α‐helix motif, on FXI secretion.